Complete Chloroplast Genomes and Comparative Analyses of Three Ornamental Impatiens Species - Luo, Chao; Huang, Wulue; Yer, Huseyin; Kamuda, Troy; Li, Xinyi; Li, Yang; Rong, Yuhong; Yan, Bo; Wen, Yonghui; Wang, Qiong; Huang, Meijuan; Huang, Haiquan (Frontiers in Genetics, 2022)
Impatiens L., the largest genus in the family Balsaminaceae with approximately 1000 species, is a controversial genus. Due to the conflict of morphological features and insufficient genomic resources, the studies of systematic evolution and understanding of taxonomic identification are considered to be very limited. Hence, we have sequenced the complete chloroplast genomes of three ornamental species (Impatiens balsamina, I. hawkeri, and I. walleriana) , and compared them with previously published wild species data. We performed a detailed comparison of a highly similar basic structure, size, GC content, gene number, order, and functional array among them. Similarly, most divergent genes were detected from previous work in the literature. The mutational regions containing highly variable nucleotide hotspots were identified and may be used as potential markers for species identification and taxonomy. Furthermore, using whole chloroplast genome data to analysis the phylogenetic relationship of the Balsaminaceae species, we found that they were all part of a single clade. The three phenotypically different ornamental species were clustered together, suggesting that they were very likely to be closely related. We achieved and characterized the plastid genome structure, identified the divergence hotspots, and determined the phylogenetic and taxonomic positions of the three cultivated species in the Impatiens genus. The results may show that the chloroplast genome can be used to solve phylogenetic problems in or between the Impatiens genus and also provide genomic resources for the study of the Balsaminaceae family's systematics and evolution.